Predict of Lost Time at Traffic Lights Intersection Road Using Image Processing - Prasetyo Isnomo, Yoyok Heru (PROCEEDING IC-ITECHS 2014, 2014)
There are three lamps in traffic lights, green, red, and amber. The amber lamp is a signfor driver as preparing to move when they are stopping because the red lamp turn on, and as emptying vehicles when the phase of traffic lights turn on green, and the moment is called as lost time. Generally, the amber time is regulated manualyl and constant, but the fact that lost time is not constant. By using CCTV IP IR we can determine speed of vehicle, so we can calculate lost time in real time. The sequence of method is used in this paper to predict and determine speed of vehicle : formulation determination to convertÂ Â  distance on image into actual distance in unit meter; pattern recognition of vehicles, in this research using previous research; time depth determination of the first capturing traffic until the second capturing; speed calculation of each vehicles types, and average of vehicles speed; calculation of lost time. The result of the algorithm aplying show that system can predict the speed of the vehicle, by using velocity formulation the system can determine lost time in automatically.